Non- Pharmacological Measures for Control of Hypertension in Geriatric Population - Sahoo, Debalina; Gosai, Harshida; Sahoo, Ujjwal; Harsoda, JM (Journal of Bangladesh Society of Physiologist, 2015)
Background: Increased prevalence of hypertension in all over the world is well recognized. Hypertension affects almost all body organs and systems. It can be managed by using nonpharmacological measures as well. Objective: To assess knowledge of non-pharmacological measures to control of hypertension and its application in geriatric hypertensive population. Methods: The study was conducted in the Department of Physiology, Sumandeep Vidyapeeth University, Vadodara. Total 108 hypertensive patients had been included for this study. Subjects were administered pre tested ten questionnaires. They responded the questionnaires at the same time, without any discussion. Results: Knowledge about normal level of blood pressure was lacking in 70% of study population. Conclusion: Knowledge about weight reduction, regular exercise, fruits and vegetables intake was poor. About half of the study population said that blood pressure can be controlled by using of drugs only. So, they were not aware of non-pharmacological measures. DOI: http://dx.doi.org/10.3329/jbsp.v9i2.22804 Bangladesh Soc Physiol. 2014, December; 9(2): 94-97